Internal control, risk and Sharīʿah non-compliant income in Islamic financial institutions - Mustafa Mohd Hanefah; Muhammad Iqmal Hisham Kamaruddin; Supiah Salleh; Zurina Shafii; Nurazalia Zakaria (ISRA International Journal of Islamic Finance, 2020)
Purpose: The existence of internal control for Sharīʿah-compliance promotes reasonable assurance that the Islamic financial institution's (IFI's) objectives are achieved in the following categories, namely, the effectiveness and efficiency of operations, the reliability of financial reporting and the level of compliance with applicable laws and regulations, as well as accounting and auditing standards. Sharīʿah non-compliant income (SNCI) is an important issue in IFIs' operations. Thus, The purpose of this paper is to identify issues related to governance and internal control of SNCI in selected IFIs in Malaysia. Design/methodology/approach This research uses a case study approach to gather data on the measures of governance and risk management in relation to the internal control for SNCI in IFIs. Interviews were conducted with officers of the Sharīʿah and internal audit departments on internal control practices regarding SNCI. Findings Regulator's guidelines on SNCI are simple and brief, lacking rigour in terms of governance, risk management and audit procedures. The section on SNCI is only a brief statement within the Bank Negara Malaysia's Guidelines on Financial Reporting for Islamic Banking Institutions and also in the Operational Risk Integrated Online Network system operated by IFIs. Most of the respondents in the interviews suggested that there should be a proper guideline in determining the classification of SNCI. Second, although IFIs have established the purification account to manage SNCI, the real practice varies from one IFI to another. Third, although there are supposedly documented procedures established in relation to management and administration of SNCI, the following events still occur in practice, namely, no authorisation from the Sharīʿah Committee (SC) on various types of income channelled to the SNCI account; unauthorised use of SNCI for other Purpose:s; SNCI not being reported in the annual financial reports; and distribution of SNCI prior to obtaining the SC's consent. Fourth, there is an absence of Sharīʿah risk assessment conducted on operational risk by IFIs to identify any potential Sharīʿah non-compliant event. Research limitations/implications This research contributes to the importance of Islamic corporate governance theory and Sharīʿah risk management, as well as strengthening the case for reporting SNCI to shareholders. It also contributes to the body of knowledge on the capability of the management in managing the internal control system of IFIs' SNCI. Originality/value A new internal control assessment matrix is proposed for Sharīʿah-compliance in IFIs.
Keywords: 330; Internal control; Islamic financial institutions (IFIs); Sharīʿah audit; Sharīʿah governance; Sharīʿah non-compliant income; Sharīʿah risk